the reality of the organizational excellence of the administrative bodies of Baghdad sports clubs through coach’s views - Hamed, Ahmed; Makki, Ali (Journal of Physical Education, 2023)
The purpose of this research is to know the reality of the organizational excellence of the administrative bodies of Baghdad sports clubs through coach’s views. The two researchers used the descriptive approach in the survey method to suit the nature of the problem. After reviewing many studies and researches, the tow researcher build an organizational excellence standard and carry out the scientific steps to build the standards including choosing the demolition of the standard and the concept of it, choosing the fields and presenting them to the experts, formulating phrases for the fields and presenting them to the experts, subjecting the phrases to scientific transactions and applying the exploratory experiment, and then finally the main building. The researchers used the statistical package for social sciences (SPSS) program in order to extract the results of the research, which showed that the sample had obtained a result of moral significance, which indicates that they possess organizational excellence. The researchers have reached many results, the most important administrative field which the sample is needed to handled and strengthen is the modern field technology whereas loyalty field was the leaset field that needed strengthen. Keywords: Beneficiaries, Creativity, Organizational loyalty, Information technology, Olympic and Paralympic Games.